ANALISIS EFEKTIFITAS CITRA MEREK, SELEBRITI ENDORSER DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK: (Studi Empiris Pada Produk Merek Garnier) - Anggun; Ambardi, Ambardi (Jurnal Ilmu Manajemen Retail Universitas Muhammadiyah Sukabumi, 2023)
Garnier Cosmetics is a leading brand with a wide range of products that can be used to meet the skin care needs of consumers. The purpose of this study is to find out the effect of brand image celebrity endorser and price on the purchase decision of Garnier brand cosmetics. The method of this study is to use a quantitative method. Distribute the questionnaire to a sample of 59 respondents which is a data collection technique using a survey technique. Data analysis using structural equation modeling. The results of this study is variable proved to have a positive and significant effect on the purchase decision. The results of each positive variabel value and r-squared value of 0,941 or 94,1% indicate that the purchase decision selection variable is declared significant.